2012
DOI: 10.1371/journal.pone.0035709
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Regulates Osteoblast Proliferation through Integrin-Mediated ERK Activation

Abstract: Mechanical strain plays a critical role in the proliferation, differentiation and maturation of bone cells. As mechanical receptor cells, osteoblasts perceive and respond to stress force, such as those associated with compression, strain and shear stress. However, the underlying molecular mechanisms of this process remain unclear. Using a four-point bending device, mouse MC3T3-E1 cells was exposed to mechanical tensile strain. Cell proliferation was determined to be most efficient when stimulated once a day by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 57 publications
4
79
0
4
Order By: Relevance
“…Several recent studies have indicated that overloaded strain could lead to pathological bone modeling, remodelling, or microdamage that might result in fractures when they accumulated [21, 22]. Previous studies have shown the mechanical strain of 5000 µε inhibited MC3T3-E1 cell proliferation [23]. In this study, the overload osteoblast damage model was constructed by stimulating MC3T3-E1 cells with a four-point bending device.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have indicated that overloaded strain could lead to pathological bone modeling, remodelling, or microdamage that might result in fractures when they accumulated [21, 22]. Previous studies have shown the mechanical strain of 5000 µε inhibited MC3T3-E1 cell proliferation [23]. In this study, the overload osteoblast damage model was constructed by stimulating MC3T3-E1 cells with a four-point bending device.…”
Section: Discussionmentioning
confidence: 99%
“…Since we know that RAS-ERK pathway is involved in mechanical signal transduction [28,44]. We asked what is the role of NF1 in osteoblast during mechanical stress.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the Nf1 gene has been knocked-out using the Cre-LoxP system under the control of 2.3 kb collagen1-alpha1 promoter (Col11), which is primarily expressed in osteoblast [23,25]. Our current view of the NF1 bone pathology, based on the analysis of osteoblast function, whether the imbalance of bone homeostasis and improper response of osteoblast cell to mechanical stress cause the NF1 skeletal manifestations [26][27][28][29][30][31][32][33][34][35].…”
Section: Signaling In Nf1 Osteoblast Cellsmentioning
confidence: 99%
“…miRNAs also activate multiple signaling pathways. The mitogen-activated protein kinase (MAPK) signaling pathway plays an important role in the osteogenic differentiation of mesenchymal stem cells in response to mechanical strain [Yan et al, 2012]. The Wnt signaling pathway is required for the osteogenic response to mechanical loading [Tu et al, 2012].…”
Section: Discussionmentioning
confidence: 99%